2016
DOI: 10.1016/j.yebeh.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different physical exercise programs on susceptibility to pilocarpine-induced seizures in female rats

Abstract: In epilepsy, the most common serious neurological disorder worldwide, several investigations in both humans and animals have shown the effectiveness of physical exercise programs as a complementary therapy. Among the benefits demonstrated, regular exercise can decrease the number of seizures as well as improve cardiovascular and psychological health in people with epilepsy. While many studies in animals have been performed to show the beneficial effects of exercise, they exclusively used male animals. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Of the studies, 10 (337 animals) analyzed the behavior manifestation following chemoconvulsants. Of 7 studies reporting latency for the first motors signs or first seizure, four studies showed increased latency (28,29,35,41) and three studies did not find significant alterations following exercise (34,40,42).…”
Section: Behavioral Analysismentioning
confidence: 97%
See 4 more Smart Citations
“…Of the studies, 10 (337 animals) analyzed the behavior manifestation following chemoconvulsants. Of 7 studies reporting latency for the first motors signs or first seizure, four studies showed increased latency (28,29,35,41) and three studies did not find significant alterations following exercise (34,40,42).…”
Section: Behavioral Analysismentioning
confidence: 97%
“…In relation to the intensity of motor signs, six of ten investigations reported lower intensity following physical exercise (28,(37)(38)(39)(40)(41), one registered higher intensity in voluntary but not in forced exercise (42), one reported no significant difference (29), and two did not analyze this parameter (34,35).…”
Section: Behavioral Analysismentioning
confidence: 99%
See 3 more Smart Citations